Legal Awareness of Generation Z Regarding the Ban On Online Gambling in Indonesia: Case Study of Generation Z in the Cilandak Area of South Jakarta: Kesadaran Hukum Generasi Z tentang Larangan Perjudian Online di Indonesia: Studi Kasus Generasi Z di Kawasan Cilandak Jakarta Selatan - Devina, Shalma; Suartini, Suartini (Dame Journal of Law, 2026)
This study aims to examine the level of legal awareness of Generation Z towards the prohibition of online gambling in Indonesia, with a focus on the Cilandak area, South Jakarta. The method used in this research is a qualitative study with empirical methods involving interviews with community leaders, school and village officials, and the distribution of questionnaires to Generation Z respondents. Data analysis was conducted to identify the level of legal understanding, forms of involvement, as well as perceptions of law enforcement and the effectiveness of the reporting system. The results show that the majority of respondents have good legal awareness and understand the risks and legal basis for prohibiting online gambling. However, vulnerability was also found in a small number of respondents who did not have a deep understanding and began to be exposed to gambling practices. The weakness of the monitoring system, the lack of continuous legal education, and the lack of optimal synergy between stakeholders are the main challenges in prevention. Therefore, a comprehensive strategy based on education, technology, and collaborative law enforcement is needed to build comprehensive protection for young people in the digital era.